2019
DOI: 10.5114/fn.2019.89855
|View full text |Cite
|
Sign up to set email alerts
|

Cepharanthine promotes the effect of dexmedetomidine on the deposition of β-amyloid in the old age of the senile dementia rat model by regulating inflammasome expression

Abstract: Aim of the study: The present study evaluates the synergistic effect of cepharanthine (CP) with dexmedetomidine (DEM) on the deposition of β-amyloid (Aβ) in the brain tissue of senile dementia (SD) rats. Material and methods: Senile dementia was induced by injecting D-gal intraperitoneally 60 mg/kg/day for six weeks and Aβ1-42 (5 µl) intracranially. The effect of cepharanthine and dexmedetomidine was estimated by determining the cognitive function and neurological function score. Moreover, mediators of inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It has been shown that biphasic amyloidotic symmetrical papular lesions (amyloid moss) were significantly flattened after 6 months of topical treatment with cepharanthine [ 225 ]. Cepharanthine was able to selectively inhibit the binding of β-amyloid oligomers to EphB2 [ 226 ] and improve the deposition of β-amyloid (Aβ) and NLRP3 [ 227 ], which may be a potential treatment for Alzheimer’s disease. In a rat model of Alzheimer’s disease, cepharanthine was also found to improve β-amyloid (Aβ) deposition.…”
Section: Activity and Use Of Cepharanthinementioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that biphasic amyloidotic symmetrical papular lesions (amyloid moss) were significantly flattened after 6 months of topical treatment with cepharanthine [ 225 ]. Cepharanthine was able to selectively inhibit the binding of β-amyloid oligomers to EphB2 [ 226 ] and improve the deposition of β-amyloid (Aβ) and NLRP3 [ 227 ], which may be a potential treatment for Alzheimer’s disease. In a rat model of Alzheimer’s disease, cepharanthine was also found to improve β-amyloid (Aβ) deposition.…”
Section: Activity and Use Of Cepharanthinementioning
confidence: 99%
“…In a rat model of Alzheimer’s disease, cepharanthine was also found to improve β-amyloid (Aβ) deposition. Moreover, its joint use with dexmedetomidine (DEM) improved symptoms in neurological function scores and cognitive function in Alzheimer’s rats [ 227 ].…”
Section: Activity and Use Of Cepharanthinementioning
confidence: 99%
See 1 more Smart Citation
“…Dexmedetomidine improved cognitive function in AD mice by increasing miR-129 expression, which targets YAP1 and distrurbs its interaction with JAG1, resulting in decreased YAP1 and JAG1 expression, leading to suppressed oxidative stress and neuronal apoptosis (Sun et al, 2020). In rats with senile dementia, the combination of cepharantine and dexmedetomidine provided a synergistic neuroprotective effect by reducing β-amyloid deposition, inflammation, and oxidative stress, via inhibiting the NLRP3-apoptotic signalling pathway (Wu et al, 2019).…”
Section: Neuroprotective Effect Of Dexmedetomidine In a Model Of Neurodegenerationmentioning
confidence: 99%
“…50 Cepharanthine also displayed cognitive enhancing properties, especially when associated with dexmedetomidine. 51 Rats of a senile dementia model receiving cepharanthine alone or in combination scored higher in assays of cognitive and neurological functions.…”
mentioning
confidence: 99%